2009
DOI: 10.1016/j.ajhg.2009.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CANT1 Mutations in Desbuquois Dysplasia

Abstract: Desbuquois dysplasia is a severe condition characterized by short stature, joint laxity, scoliosis, and advanced carpal ossification with a delta phalanx. Studying nine Desbuquois families, we identified seven distinct mutations in the Calcium-Activated Nucleotidase 1 gene (CANT1), which encodes a soluble UDP-preferring nucleotidase belonging to the apyrase family. Among the seven mutations, four were nonsense mutations (Del 5' UTR and exon 1, p.P245RfsX3, p.S303AfsX20, and p.W125X), and three were missense mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
106
1
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(126 citation statements)
references
References 15 publications
6
106
1
8
Order By: Relevance
“…Recently, Huber et al 4 identified mutations in the gene encoding the calcium-activated nucleotidase 1 (CANT1) in DBQD type 1, which is followed by Faden et al 5 We also found CANT1 mutations in DBQD type 2 and Kim variant. In our series, we identified CANT1 mutations in all seven patients from five unrelated families with DBQD Kim variant, and all patients had c.676G4A (p.V226M).…”
Section: Introductionmentioning
confidence: 60%
“…Recently, Huber et al 4 identified mutations in the gene encoding the calcium-activated nucleotidase 1 (CANT1) in DBQD type 1, which is followed by Faden et al 5 We also found CANT1 mutations in DBQD type 2 and Kim variant. In our series, we identified CANT1 mutations in all seven patients from five unrelated families with DBQD Kim variant, and all patients had c.676G4A (p.V226M).…”
Section: Introductionmentioning
confidence: 60%
“…Early (perinatal) lethality in four of these patients was associated with nonsense mutations. 12 Very recently, mutations in the CANT1 gene have also been found associated with the DBQD type 2, as well as with the so called 'Kim variant' of DBQD. 13 …”
Section: Introductionmentioning
confidence: 99%
“…Calciumactivated nucleotidase 1 gene mutations have been identified in nine families with Desbuquois type 1, a gene that hydrolyses UDP followed by guanosine diphosphate and UTP [466].…”
Section: Desbuquois Dysplasiamentioning
confidence: 99%